Environmental and Socially Related CSR practices in Sri Lanka: Insights from Annual Report Disclosures - Fernando, A.J (RMIT, 2018)
Purpose- The purpose of the research is to examine the nature and extent of environmental and social practices of public companies in Sri Lanka in terms of Corporate Social Responsibility (CSR). The study also aims to identify and evaluate trends and the features of CSR reporting by companies listed on Colombo Stock Exchange (CSE). Design/methodology/approach- The study was carried out under three phases. The first phase related to the year 2016 and involved an analysis of annual reports all 292 companies registered on the CSE for the year 2016. The second phase analysed the annual reports or sustainability reports of 156 companies which have been identified in phase 1 as CSR reporting companies in Sri Lanka. The contents of annual reports of 16 companies were fully analysed to determine the trend in CSR practices for the 5 years from 2012 to 2016. Findings- Findings revealed that environmental developments are disappointing and many businesses in Sri Lanka have still not properly engaged in CSR practices in relation to environmental matters. Overall, business engagement in socially-related CSR practices is at a reasonable level, but not environmental CSR practices. Originality/Value- This paper offers initial insights on environmental and socially related CSR disclosure practices in Sri Lanka.
Keywords: CSR, Content analysis, Colombo Stock Exchange, GRI Sustainability database